Comparison of Attitudes of Male learners and Women Based on Pancasila Student Profile During Limited Face-to-Face Learning - Diah Puji Nali Brata; Edy Setiyo Utomo (STAI Miftahul Ula Nganjuk, 2022)
The purpose of this study was to find out the comparison of Pancasila student profile-based attitudes between male and female learners during limited face-to-face learning. This research method uses a quantitative approach. The study sample consisted of 278 learners, of which 137 were men and 141 were women. The research instrument consists of questionnaires given online. Analysis questionnaire results to find out the comparison of attitudes with IBM SPSS 24.0. The results showed that in the dimension of Iman attitudes, the average assessment of the attitude of male learners amounted to 2.54, and the average assessment of the attitude of female learners amounted to 2.63. There was a significant difference between male and female learners in assessing the attitude of faith, which refers to the results of the calculation of SPSS 24.0 compared to other dimensions of attitudes. Limited face-to-face learning impacts the value of attitudes such as self-study patterns, the collaboration between learners, the acquisition of information, especially materials to support education, thought processes, reflecting on thought independently, how to evaluate, and attitudes to make decisions. Teachers are expected to still provide performance and attitude models that refer to the value of character in such a way that it can be used as a good habit by learners who are integrated with technology during limited face-to-face learning